Behavior of the water/vapor interface of chitosan solutions with an anionic surfactant: effect of polymer–surfactant interactions. Issue 40 (13th October 2020) - Akanno, Andrew; Guzmán, Eduardo; Ortega, Francisco; Rubio, Ramón G.
Abstract : Adsorption of chitosan–sodium laureth sulfate mixtures at the water/vapor interface appears very different to that of other oppositely charged polyelectrolyte–surfactant mixtures. Abstract : The adsorption of mixtures formed by chitosan and sodium lauryl ether sulfate (SLES) at the water/vapor interface has been studied on the basis of their impact on the equilibrium surface tension of the interface, and the response of such an interface to mechanical deformations. The analysis of the surfactant binding to the chitosan chains evidenced that the chitosan–SLES solutions were mixtures of polyelectrolyte–surfactant complexes and a non-negligible amount of free surfactant molecules. The interfacial properties showed two well-differentiated regions for interfacial adsorption as a function of the SLES concentration: (i) at a low surfactant concentration, co-adsorption of chitosan and SLES occurs, and (ii) at high concentrations, the surface is mostly occupied by SLES molecules. This behavior may be interpreted in terms of a complex equilibration mechanism of the interfacial layers, where different coupled dynamic processes may be involved. Furthermore, the use of the time–concentration superposition principle has confirmed the different dynamic behaviors of the chitosan–SLES adsorption as a function of the SLES concentration. This work sheds light on some of the most fundamental bases governing the physico-chemical behavior of mixtures formed by a biopolymer and a surfactant, where their complex behavior is governed by an intricate balance of bulk and interfacial interactions.